1999
DOI: 10.1016/s1097-2765(00)80461-x
|View full text |Cite
|
Sign up to set email alerts
|

Internuclear Gene Silencing in Phytophthora infestans

Abstract: Transformation of the diploid oomycete plant pathogen Phytophthora infestans with antisense, sense, and promoter-less constructs of the coding sequence of the elicitin gene inf1 resulted in transcriptional silencing of both the transgenes and the endogenous gene. Since heterokaryons obtained by somatic fusion of an inf1-silenced transgenic strain and a wild-type strain displayed stable gene silencing, inf1 silencing is dominant and acts in trans. Inf1 remained silenced in nontransgenic homokaryotic progeny fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
133
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 46 publications
8
133
0
Order By: Relevance
“…If single-copy loci continuously generate sense and antisense transcripts, tandem repeats are not necessary for maintaining the silenced state; the resulting dsRNA would be cleaved into siRNAs, which would then establish the altered chromatin state. Paramutation in Phytopthora infestans 60 is most consistent with a trans-RNA model. Silencing of an endogenous gene by an homologous transgene occurs when the genes are in different nuclei in the heterokaryon, indicating a mobile trans-acting signal.…”
Section: Evolution Of Polyploidssupporting
confidence: 63%
See 1 more Smart Citation
“…If single-copy loci continuously generate sense and antisense transcripts, tandem repeats are not necessary for maintaining the silenced state; the resulting dsRNA would be cleaved into siRNAs, which would then establish the altered chromatin state. Paramutation in Phytopthora infestans 60 is most consistent with a trans-RNA model. Silencing of an endogenous gene by an homologous transgene occurs when the genes are in different nuclei in the heterokaryon, indicating a mobile trans-acting signal.…”
Section: Evolution Of Polyploidssupporting
confidence: 63%
“…Trans-interactions were described between two homologous transgenes 57,83,84 , and between transgenes and endogenous genes 60,62 .Where tested, transcription was shown to be altered 57,80,84,85 and the alleles or homologous sequences often showed differences in chromatin, such as DNA methylation and/or NUCLEASE HYPERSENSITIVITY 3,24,83,86 .We now know that paramutation involves trans-interactions between homologous sequences that establish distinct heritable chromatin changes and that paramutation is not limited to plants; similar phenomena have been described in organisms from several other kingdoms (TABLE 1) pl1 loci occurs with 100% penetrance. Rare, darkly pigmented F 1 plants potentially carry dominant mutations that prevent the establishment of paramutation; rare F 2 families segregating darkly pigmented plants might carry recessive mutations that fail to maintain the low expression levels that are associated with paramutation and could affect maintenance of the paramutagenic state.…”
mentioning
confidence: 99%
“…Following transformation of P. infestans with sense, antisense, and promoterless constructs of the endogenous single-locus inf1 gene, silencing of inf1 was observed in as many as 20% of the transformants (107). Silencing was accompanied by the complete absence of inf1 mRNA and INF1 protein and proved stable over repeated vegetative cultures of the pathogen both in vitro and in products (44,107). The mechanism of gene silencing is largely unknown; however, nuclear run-on assays have indicated that silencing is regulated at the transcriptional level (107).…”
Section: Molecular and Genomic Resourcesmentioning
confidence: 99%
“…Silencing was accompanied by the complete absence of inf1 mRNA and INF1 protein and proved stable over repeated vegetative cultures of the pathogen both in vitro and in products (44,107). The mechanism of gene silencing is largely unknown; however, nuclear run-on assays have indicated that silencing is regulated at the transcriptional level (107). No hypermethylation was observed in either transgenic or endogenous sequences of inf1 (107), but alterations in heterochromatin formation in regions surrounding silenced genes have been noted recently (P. van West, personal communication).…”
Section: Molecular and Genomic Resourcesmentioning
confidence: 99%
“…Transnuclear transcriptional gene silencing in Phytophthora infestans is diffusible and dominant but does not involve siRNA molecules. Rather, it has been demonstrated that DNA methylation is required for the silencing effect (van West et al 1999(van West et al , 2008.…”
mentioning
confidence: 99%